Improved planning of large dam operation: Using decision support systems to optimize livelihood benefits, safeguard health and protect the environment - McCartney, Matthew P. (CGIAR Challenge Program on Water and Food, 2009)
Improved Planning of Large Dam Operation: Using Decision Support Systems to Optimize Livelihood Benefits, Safeguard Health and Protect the Environment. This project was undertaken with the aim of providing information to assist policy-makers, water resource managers and other interested stakeholders in the planning and management of large dams in Africa. The project highlighted the importance of considering environmental and social (including health) issues in dam planning and operation and illustrated how contemporary Decision Support Systems can be used to assist decision making processes. Key project findings relate to: i) the importance of stakeholder involvement in decision-making and how to enhance it; ii) the effectiveness of EIA follow-up; iii) the malaria implications of large dam construction; iv) the simulation of environmental impacts of large dam development and v) estimates of environmental flows. Guidelines on the use of DSS for key aspects of dam planning and operation have been developed.